Membangun Desa Daenaa Melalui Optimalisasi Pemanfaatan Hasil Pertanian dan Limbahnya dalam Mendukung Pencapaian Sustainable Development Goals (SDGs) - Julhim S Tangio; Lukman A.R. Laliyo; Masrid Pikoli; Siti Nurqomariah Riva’i; Siti Amalisa Ishak (Damhil: Jurnal Pengabdian kepada Masyarakat, 2022)
Village development is one of the duties and responsibilities of higher education which is manifested in the Tri Dharma of Higher Education, namely community service. Gorontalo Province is an area where most people work as farmers with low incomes. The people of Daenaa Village are corn farmers. Corn production is only sold in the form of raw dry corn materials without going through processing into products of nutritional value with high selling prices. Lack of understanding and not knowing the right technology to process raw corn materials into processed food products that are creative and have economic value. Processing of corn and its waste is aimed at increasing its usefulness and selling value. The implementation of the MBKM KKN Program is a solution to help the community and village government in building sustainable villages or Sustainable Development Goals, creating and increasing community knowledge, and encouraging the realization of independent villages. The method used is the method of training and mentoring, through four stages, namely the preparation stage, the implementation stage, the monitoring and evaluation stage, and the reporting stage.